2016
DOI: 10.1186/s12889-016-3654-0
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities for recovery at work and excellent work ability - a cross-sectional population study among young workers

Abstract: BackgroundBetter opportunities for recovery at work are thought to be associated with work ability in a young workforce but evidence is scarce to lacking. The aim of this study was to examine cross-sectional associations between opportunities for recovery at work and excellent work ability among young workers and specifically for young workers with high work demands.MethodsA study group of 1295 women and 1056 men aged 18–29 years was selected from three biennial years of a population cohort. The subsample repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…The development and validation of the method was described by Statistics Sweden [ 12 ]. Previous studies also reported data from this survey, for example Boström et al [ 13 ]. We used the 2011 data.…”
Section: Methodsmentioning
confidence: 83%
See 2 more Smart Citations
“…The development and validation of the method was described by Statistics Sweden [ 12 ]. Previous studies also reported data from this survey, for example Boström et al [ 13 ]. We used the 2011 data.…”
Section: Methodsmentioning
confidence: 83%
“…In this study, we chose a way of operationalizing recovery opportunities similar to that used by Boström et al [ 13 ]. However, we did not look at the different aspects of recovery opportunities separately as was done in that study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, self-regulation is associated with healthy nutrition and exercise ( Shieh et al , 2015 ). In addition, research indicates that recreational opportunities are associated with higher work ability in young employees ( Boström et al , 2016 ). Young workers’ ability to self-regulate between phases of high workload and relaxation should therefore be supported.…”
Section: Discussionmentioning
confidence: 99%
“…Low chronic inflammation is related to the development of cardiovascular diseases. [10][11][12][13][14][15][16][17][18] These problems can be avoided by optimal work process development. Having varied work activities and the possibility of deciding when to perform a work task, as well as being able to decide working hours can contribute to excellent workability.…”
Section: Discussionmentioning
confidence: 99%